RUMINAL DEGRADABILITY CHARACTERISTICS IN ANIMAL PROTEIN SOURCES OF PAKISTAN - I. B. Marghazani; M. A. Jabbar; T. N. Pasha; M. Abdullah (Journal of Animal and Plant Sciences, 2013)
Study on ruminal degradability characteristics of six different animal protein sources found in Pakistan was carried out through in situ procedure using rumen fistulated Nili-Ravi buffalo steer. Samples of fish meal, poultry byproduct meal, meat meal, bone meal, feather meal and blood meal were obtained from 10 different locations. Crude protein (CP) ruminal degradability was determined at 0, 3, 6, 12, 24 and 48 hours in triplicate. Data obtained at different hours of ruminal incubation were fitted to Orskov and McDonald equation to determine fractions a, b, degradation rate and effective degradability at 2, 5 and 8 percent. In CP ruminal degradation kinetics, both fractions “a” and “b” were significantly varied (P<0.001) while, CP degradation rate was statistically similar. Effective CP degradability at different rumen passage rates (0.02, 0.05, 0.08 %) were significantly varied (P<0.001). The effective degradability was less than 50% at 5% rumen passage rate in all studied animal protein sources.
Keywords: Ruminal degradability; animal protein sources; undegradable protein; Nili- Ravi buffalo